Inhibition of Zea mays coniferyl aldehyde dehydrogenase by daidzin: A potential approach for the investigation of lignocellulose recalcitrance. (March 2020) - Ferro, Ana Paula; Flores Júnior, Rogério; Finger-Teixeira, Aline; Parizotto, Angela Valderrama; Bevilaqua, Jennifer Munik; Oliveira, Dyoni Matias de; Molinari, Hugo Bruno Correa; Marchiosi, Rogério; dos Santos, Wanderley Dantas; Seixas, Flávio Augusto Vicente; Ferrarese-Filho, Osvaldo
Graphical abstract: Highlights: Three-dimensional structure of Zmays CALDH was modeled. Daidzin was selected from a set of 20 putative inhibitors of the enzyme. In silico and in vitro findings indicate that daidzin is a competitive inhibitor. An alternative approach for studies on lignocellulose recalcitrance is suggested. Abstract: Coniferyl aldehyde dehydrogenase (CALDH) catalyzes the oxidation of coniferyl aldehyde to ferulic acid. Because ferulic acid has a relevant role in the structure and recalcitrance of the cell wall, inhibition of CALDH can reduce its levels and increase the digestibility of lignocellulosic biomass. We prospected in silico a selective inhibitor of CALDH of Zea mays . The Zmays CALDH gene was identified by homology with the corresponding gene of Arabidopsis thaliana . The sequence was translated and analyzed, and the quaternary structure was modeled. A set of 20 putative inhibitors were screened from a virtual library and docked in the active site of Zmays CALDH, and daidzin (DZN) was selected as an enzyme inhibitor. The stability of the Zmays CALDH–DZN complex was evaluated by molecular dynamics simulations of the monomeric and tetrameric forms. For evaluation of kinetic analysis, Zmays CALDH activity was determined in vitro by high-performance liquid chromatography. In comparison to the DZN-free control, the data obtained indicated constant V max and enhanced K m . Altogether, in silico and in vitro findings indicated that DZN inhibited Zmays CALDH competitively. The DZN-induced inhibition of Zmays CALDH could be a valuable and promising approach to studies on ferulic acid biosynthesis and saccharification of lignocellulosic biomass.